ESP (english for specific purposes) vocabulary to improve reading at an a1.2/ a2.1 english level - Aulestia Vallejo, Luis Enrique (2021)
The aim of this research was to investigate the use of ESP vocabulary in general English classes to improve English, by using the student-centered learning approach, concentrating mainly on reading skills. For the study case, 123 students of different careers offered at Central University of Ecuador, English A1.2, A2.2 levels, constituted the population studied, during the period May-November 2018. A teacher- made pre-test of basic technical vocabulary knowledge was administered. ESP vocabulary was taught to complement General English structures and grammar.  At the end of the semester, a post-test was given to the students to determine the influence of the technical vocabulary in their proficiency.  Data analysis showed that the student-centered approach using basic technical vocabulary in general English learning was effective.  Furthermore, the results showed that when focusing to student’s needs, degree program students are more motivated to learn and read more academic literature related to their careers.